Analysis of the Determinants of Profitability of Sharia General Banking in Indonesia - Dzaky, Muhammad Raihan; Wildana, Muhammad Dandy Alif (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The Islamic banking industry in Indonesia has experienced significant growth in recent years, both in terms of the number of institutions and total assets managed. However, its contribution to the national banking market share remains relatively low. One of the main challenges faced is how to maintain optimal and sustainable profitability levels. Profitability is a crucial indicator reflecting the efficiency of performance and the effectiveness of asset management in generating profits. This study aims to analyze the factors influencing the profitability of Islamic commercial banks in Indonesia for the 2018-2023 period. The results of this study indicate that of the four independent variables, only one variable has a significant effect on the dependent variable, namely the OE/OI variable, with a negative direction. Meanwhile, the NPF, FDR, and CAR variables do not affect the profitability of Islamic commercial banks in Indonesia. These results are expected to provide strategic contributions in managerial decision-making, policy formulation by regulators, and the development of academic literature in the field of Islamic finance, especially in understanding the factors that influence the performance and sustainability of Islamic banking in Indonesia.